Penerimaan Diri, Dukungan Sosial dan Kebahagiaan Pada Lanjut Usia - Uraningsari, Fitrie; Djalali, M As’ad (Persona:Jurnal Psikologi Indonesia, 2016)
The purpose of this study to examine the relationship between self-acceptanceand social support and happiness in the elderly community. Research variables weremeasured using a scale of self-acceptance, social support scale and the scale ofhappiness. Subjects were 90 elderly spread over the area Ketintang, Rungkut andSidoarjo, ages 65 years and older. Data were analyzed using regression analysis. Theresults showed that the variables of self-acceptance and social support associated withhappiness. Where happiness has a significant relationship with self-acceptance andsocial support with results in F = 25.084 and p = 0.00 (p <0.01). With the obtainedpartial test Parthia r = 0,143l and t = 1.356, p = 0.178 (p> 0.05) means there is noconnection between self-acceptance with happiness. Social support relationships withhappiness obtained partial r = 0.424 and t = 2.728, p = 0.008 (p <0.001), meaning thereis a positive relationship between social support and happinessKeywords : self-acceptance, social support, happiness